Evaluation from the effects of the myofascial release over the diaphragm muscle (Research, Society and Development, 2021)
Objective: Evaluate the effects from the Instrument Assist Soft Tissue Mobilization (IASTM) Gustavo Pilon Concept, the instrumental method of myofascial manipulation, over the diaphragm muscle. Methodology: study accomplished with a volunteer from the feminine sex, with 21 years old, resident in the Uruguaiana/RS city. She underwent respiratory muscle strength assessment and a diaphragm ultrasound evaluation, before and after the intervention, in which were applied the myofascial instrumental release method technique, Gustavo Pilon Concept. Results: Regarding the respiratory muscle strength, translated by the Maximum Inspiratory Pressure (MIP) and the maximal expiratory pressure (MEP), it was verified, respectively at 3 momentums (M1, M2, M3): MIP of 119cmH 2 O, 95cmH 2 O and 95cmH2O; MEP of 112cmH2O, 102cmH2O and 109cmH2O. Furthermore, in relation to the Muscle Thickness (MT), where formed 3 measures in each momentum, to know: M1 as MT of 2,4cm, 2,4mm and 2,4cm; M2 as MT of 2,4cm, 2,4cm and 2,3cm; also M3 as MT of 2,8cm, 2,8cm and 2,8cm. Conclusion: In the present study there was no increase in the respiratory muscle strength between the evaluated momentums. Regarding the diaphragm thickness, in only one intervention, was verified an improvement in the diaphragm muscle length.